Delivering affordable cancer care in the 21st Century : workshop summary - Balogh, Erin; Patlak, Margie; Nass, Sharyl J. (Online access: NCBI NCBI Bookshelf., 2013)
"Rising health care costs are a central fiscal challenge confronting the United States. National spending on health care currently accounts for 18 percent of gross domestic product (GDP), but is anticipated to increase to 25 percent of GDP by 2037. The Bipartisan Policy Center argues that "this rapid growth in health expenditures creates an unsustainable burden on America's economy, with far-reaching consequences". These consequences include crowding out many national priorities, including investments in education, infrastructure, and research; stagnation of employee wages; and decreased international competitiveness. In spite of health care costs that far exceed those of other countries, health outcomes in the United States are not considerably better. With the goal of ensuring that patients have access to high-quality, affordable cancer care, the Institute of Medicine's (IOM's) National Cancer Policy Forum convened a public workshop, Delivering Affordable Cancer Care in the 21st Century, October 8-9, 2012, in Washington, DC. Delivering Affordable Cancer Care in the 21st Century summarizes the workshop"--